Renovación paisajística y del espacio público en parques barriales sostenibles en el sector de Candido 1 - Farfán Pérez, Natalia (Universidad Antonio Nariño, 2024)
After carrying out an exhaustive analysis of the city of Neiva and the various problems that afflict it, we have identified two issues of utmost relevance: the deterioration and misuse of public space, as well as the worrying issue of global warming. In this sense, we firmly believe that both challenges can be addressed from the same perspective of action, in direct collaboration with the community. Therefore, the present proposal has as its main objective the creation of an innovative model for the renovation of public spaces in neighborhood areas. This model will not only focus on aesthetic revitalization, but will also incorporate elements designed to mitigate the effects of climate change. These elements include eco-sustainable street furniture, a landscaping design in harmony with our environmental surroundings, and the promotion of active community participation in the use, enjoyment and conservation of these public spaces. In addition, this project has as a central goal the formulation of activities that can be developed around the green spaces present in the sector Candido 1. These activities will seek to stimulate and encourage the use of these spaces, in order to strengthen the sense of belonging and cultural appropriation.